The Translation of English past perfect into Arabic in the Light of The old Man and The Sea - Malkawi , Mai Abdel Kareem Malkawi (Journal of Research in Humanities, 2023)
: This study aims to check the translation of English past perfect into Arabic. This tense is somehow problematic forming a linguistic gap because it has no Arabic correspondent, the matter that imposes on the translator to put or compose certain formula that properly conveys both the tense and the aspect of past perfect. For this purpose I took Hemingway’s The Old Man and the Sea and its translation done by Monir Balbaki in order to examine and study how the translator dealt with it.